Names of natural objects: semantic, linguocultural and typological features - Grdzelyan, Rouzan (Bulletin of Yerevan University H: Russian Philology, 2023)
The article is devoted to one of the important for the comparative-semantic, lexico-typological and linguocultural description of the classes of names - the names of natural objects. On the example of the analysis of the names of water natural objects the article presents the features of names that are important for such a description - the ratio of objectivity and attributivity in their semantic structure, the types of characteristics of these objects in discourse, some aspects of the methodology for describing the names of natural objects - analysis and comparison of dictionary entries, groups of thematically related lexemes, analysis of the corpus of texts, the semantics and word usage of derivatives. So in the main part of the article, on the example of a comparative analysis of the names of water natural objects in the Russian and Armenian languages, the features of the names under consideration that are important for such a description are presented - the ratio of objectivity and attributivity in their semantic structure, identification of a set of semantic components and their comparison, linguistic and cultural features of interlingual synonyms, as well as types of characteristics of these objects in discourse. Further analysis is based on the working hypothesis formulated in the article: when in the semantic structure of the word are the more attributive elements of meaning, then in the texts are less often the extension of the word by definitions. The final part of the article presents conclusions based on the data obtained, as well as some aspects of the methodology for describing the names of natural objects - 1) analysis and comparison of dictionary entries, aimed at identifying a set of semantic components, which, in turn, will help to establish "extra" components in one of the languages ​​under consideration, and, consequently, the semantic difference between the studied words; 2) analysis and comparison of a group of thematically related lexemes, which will help to establish the degree of taxonomic depth of the studied groups of words; 3) analysis of the corpus of texts, which makes it possible to identify the compatibility potential of lexemes, ways and means of expanding their meanings with the help of definitions, metaphors, as well as possible prohibitions imposed on the distribution of words by definitions, etc.; 4) analysis of semantics and word usage of derivatives.